After life imprisonment : reentry in the era of mass incarceration - Liem, Marieke; Sampson, Robert J., 1956- (New York : New York University Press, 2016)
"One out of every ten prisoners in the United States is serving a life sentence--roughly 130,000 people. While some have been sentenced to life in prison without parole, the majority of prisoners serving 'life' will be released back into society. But what becomes of those people who reenter the everyday world after serving life in prison? In After Life Imprisonment, Marieke Liem carefully examines the experiences of 'lifers' upon release. Through interviews with over sixty homicide offenders sentenced to life but granted parole, Liem tracks those able to build a new life on the outside and those who were re-incarcerated. The interviews reveal prisoners' reflections on being sentenced to life, as well as the challenges of employment, housing, and interpersonal relationships upon release. Liem explores the increase in handing out of life sentences, and specifically provides a basis for discussions of the goals, costs, and effects of long-term imprisonment, ultimately unpacking public policy and discourse surrounding long-term incarceration. A profound criminological examination, After Life Imprisonment reveals the untold, lived experiences of prisoners before and after their life sentences"--Provided by publisher.
Introduction -- Understanding desistance -- The context -- Lives spiraling out of control -- A life sentence -- A productive, law-abiding citizen -- Life after life imprisonment -- Residual effects of imprisonment -- Going back -- Staying out -- Reconsidering lifer reentry -- Notes.
"Study of over sixty homicide offenders who served long sentences before being released"--Foreword.
Includes bibliographical references (pages 225-259) and index.
Keywords: Prisoners -- Deinstitutionalization -- United States; Murderers -- United States; Life imprisonment -- Social aspects -- United States; Ex-convicts -- United States -- Social conditions; Ex-convicts -- United States -- Economic conditions; Recidivism -- United States